Aktivitas Penelaahan Naskah Kuno dalam Tradisi Arab Islam dan Indonesia - mohamad shofin sugito (Tsaqofah, 2018)
Manuscript is an ancestral heritage that stores various information from various aspects of life in the past. These aspects of life can include philosophy, religion, belief, maybe even technical problems in life such as building a house, teaching about skills and skills. Thus, the text has benefits and roles that are universal. That is, the contents of the text can be enjoyed or utilized by anyone, from various circles and various scientific disciplines. Indonesia is known as a country that is rich in the treasures of past retirement culture. One of them is a legacy in the form of old manuscripts with handwriting. The past manuscripts can be found in almost every area in the form of a number that is not small and the type is very varied. This short article will examine how the activities of the study of Ancient Manuscripts in the traditions of Arab Islam and Indonesia.